PHILIPPINE MSMES AFTER THE COVID-19 PANDEMIC: A SYSTEMATIC REVIEW OF PANDEMIC IMPACTS AND COPING STRATEGIES - Labiaga, Jeorgie Francine; Karl P. Campos (Ekonomi dan Bisnis: Berkala Publikasi Gagasan Konseptual, Hasil Penelitian, Kajian, dan Terapan Teori, 2024)
The COVID-19 pandemic negatively impacted the economy's flow in the majority of areas across the world. Reduced economic activity due to travel restrictions and lockdowns imposed to stop the virus's spread caused economic recessions in the pandemic-affected areas. MSMEs are the backbone of the Philippines, providing 99.5% of the nation’s business population and 65.10% of the nation's workforce. In addition to dealing with extraordinary economic and social challenges over the past two years, SME preparation for transitioning to a digital and sustainable economy has been necessary. The researcher will use a Systematic Literature Review to assess the transparency and consistency of the screening procedure and the approaches to coping applied by Philippine MSMEs in the context of the COVID-19 pandemic. The study will make use of three research guide questions. 1) What are the pandemic risks and their impact on Philippine MSMEs? 2) What coping strategies do Philippine MSMEs use to deal with risks and pandemic risk impacts? According to the review, human movement restrictions (Lockdowns), financial constraints/ revenue losses, operating difficulties, economic crisis and recession, and job losses are impacts of the pandemic on MSMEs. Furthermore, the study listed four essential coping strategies: digital and technological adoption/adaptation, government financial support/packages, modification of business models, and implications for financial stability (loans). This study will contribute to ideas in innovation and technological advancement, business improvement, and wise cost distribution.